Pemberdayaan Masyarakat Sebagai Upaya Mitigasi Lingkungan Dalam Penurunan Angka Stunting di Wilayah Kepulauan Semiringkai: Community Empowerment as an Environmental Mitigation Effort in Reducing Stunting Rates in the Semiringkai Islands Region - Junias, Marlyn Susanti; Ndoen, Enjelita Mariance; Sudarmadji, Claudya S Virlynriana; Lona, Atarini A (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Stunting is a serious health issue because it has short-term and long-term impacts on public health. NTT Province is the province with the highest stunting cases in Indonesia. Baadale Village, which is in the Rote Ndao Regency, NTT, is also not immune from the problem of stunting in toddlers and targets to be stunting-free by 2023. The problems found are the lack of knowledge of pregnant women and mothers of toddlers regarding environmental sanitation, inconsistent implementation of environmental sanitation and clean and healthy living behavior, poor parenting patterns for toddlers, and limited knowledge and practice of serving varied food menus in improving toddler nutrition. This community service activity is carried out to increase the knowledge and abilities of mothers of children under five years old regarding implementing environmental sanitation, parenting patterns, and serving a variety of food menus to reduce stunting rates. The activities include health education and providing animal protein assistance. The activity results showed an increase in knowledge of 60% in pregnant women and mothers of toddlers after the counseling. Participants were also willing to apply and pass on the knowledge gained to other pregnant women and mothers of toddlers in Baadale Village. Continuous assistance and education need to be carried out to continue to encourage the will and ability of the community, especially pregnant women and mothers of toddlers, to maintain a healthy environment and implement good parenting patterns in terms of feeding, health care, and personal hygiene for children under five years old.